Students' Information Literacy Development as a Guarantee of Qualitative Studies - Gudakovska, Iveta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Publication devoted to information literacy development updates. Information literacy competencies as the basis for the success of a human life takes on a special significance in higher education teaching. Success of this process is driven by university cooperation partners: teachers, librarians and administrations work. Teachers implement information literacy development methods courses, librarians responsible for information resources in institution make up their own training system, but the administration - facilitates the implementation of information literacy and financial support. Competencies based on governmental, professional or institutional defined standards, which can provide an overall level of information literacy development.